2013
DOI: 10.1371/journal.pone.0080869
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Preterm Birth on Exercise Capacity in Healthy Young Men: A National Population-Based Cohort Study

Abstract: BackgroundIncreasing numbers of survivors of preterm birth are growing into adulthood today. Long-term health-effects of prematurity are still poorly understood, but include increased risk for diabetes, obesity and cardiovascular diseases in adult life. To test if reduced physical fitness may be a link in the causal chain of preterm birth and diseases in later life, the association of preterm birth and adult exercise capacity was investigated. The hypothesis was that preterm birth contributes independently of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 42 publications
5
58
2
Order By: Relevance
“…Several, although not all, 40 studies have shown lower cardiorespiratory fitness among children and young people born extremely (<28 weeks) or very (<32 weeks) preterm or at extremely or very low birth weight with the use of a maximal exercise test 10,11,[40][41][42][43] or a submaximal test 8,41 as in our study. A study in 218 820 Swedish male conscripts showed that among those born at 32 to 36 weeks, maximal exercise capacity was 0.10 SD lower than among those born at term 12 ; such a small difference would not have been detected in the current study. Together with these studies, our study suggests that lower levels of cardiorespiratory fitness are not present across the whole range of preterm births, at least at any meaningful level.…”
Section: Cardiorespiratory Fitnesscontrasting
confidence: 80%
See 1 more Smart Citation
“…Several, although not all, 40 studies have shown lower cardiorespiratory fitness among children and young people born extremely (<28 weeks) or very (<32 weeks) preterm or at extremely or very low birth weight with the use of a maximal exercise test 10,11,[40][41][42][43] or a submaximal test 8,41 as in our study. A study in 218 820 Swedish male conscripts showed that among those born at 32 to 36 weeks, maximal exercise capacity was 0.10 SD lower than among those born at term 12 ; such a small difference would not have been detected in the current study. Together with these studies, our study suggests that lower levels of cardiorespiratory fitness are not present across the whole range of preterm births, at least at any meaningful level.…”
Section: Cardiorespiratory Fitnesscontrasting
confidence: 80%
“…8,11 Few studies have assessed this in adolescents or adults born closer to term; a study in Swedish male conscripts was consistent with a graded relationship between lower length of gestation and lower maximal exercise capacity. 12 This question is important because both cardiorespiratory and muscular fitness are independent predictors of cardiometabolic and musculoskeletal health [13][14][15] and lower late-life mortality. 16,17 We studied the association of early (<34 weeks) and late (34-36 weeks) preterm birth with muscular, cardiorespiratory, and self-rated physical fitness among young adults.…”
mentioning
confidence: 99%
“…To date, studies undertaken to characterise exercise capacity in adults born preterm have been relatively small with conflicting findings 47 55 67. A large population-based national cohort study of male army conscripts reported preterm birth as an independent predictor of reduced exercise capacity 67.…”
Section: Preterm Birth and Young Adult Lung Healthmentioning
confidence: 99%
“…A large population-based national cohort study of male army conscripts reported preterm birth as an independent predictor of reduced exercise capacity 67. Narang and colleagues reported no significant difference in exercise capacity between those born preterm and term controls 55…”
Section: Preterm Birth and Young Adult Lung Healthmentioning
confidence: 99%
“…Furthermore, their ability to or interest in physical activity may be affected, which may lead to a lower exercise capacity. This is further discussed in our previous study [13]. Even if exercise capacity is lower, Clemm and colleagues have shown that individuals born preterm do have the possibility to increase their exercise capacity with increased physical activity [14].…”
Section: Discussionmentioning
confidence: 77%